Diamond-graphene composite material and preparation method thereof
By seeping diamond suspension under high pressure to porous graphite prefabricated body, and using the vibration suppression process to optimize the orientation of the graphite layer, to form an amorphous transition layer, solving the problem of unstable thermal conductivity of diamond-graphite composite material and complex preparation process. , Realize the preparation of high thermal conductivity and low cost.
Patent Information
- Application Number
- CN202411576499.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-06
- Publication Date
- 2025-01-28
AI Technical Summary
The thermal conductivity of existing diamond-graphite composites is unstable, the preparation process is complex and costly.
The method of leaking diamond suspension under high pressure prefabrication under high pressure is used to optimize the orientation of the graphite sheet layer by vibrating suppression process to form an amorphous transition layer to improve the combination of interface.
The thermal conductivity of the composite material was significantly improved to 570-625W/(m · k), and the performance was stable, and the discreteness was controlled within ± 5%, reducing production costs.
Smart Images

Figure CN119371942A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of computational chemical composite materials, and in particular relates to a diamond-graphene composite material and a preparation method thereof. Background Art
[0002] As electronic and optoelectronic devices develop towards miniaturization and high power density, heat dissipation issues are becoming increasingly prominent, placing new demands on materials. In recent years, composite materials with high thermal conductivity graphite as filler have attracted more and more attention. Natural flake graphite is an ideal filler for preparing high thermal conductivity composite materials due to its abundant resources, low price and high thermal conductivity. A variety of high thermal conductivity composite materials can be prepared using diamond as the matrix and natural flake graphite as the filler.
[0003] Due to the high aspect ratio and anisotropic thermal conductivity of graphite sheets, composite materials with graphite as filler exhibit significant thermal anisotropy: the thermal conductivity in the plane parallel to the graphite sheet ( ) can reach the thermal conductivity perpendicular to the graphite layer ( ) dozens of times.
[0004] In addition, there are a variety of characterization methods to study the microstructure and properties of diamond-based-graphite filler composites, such as X-ray diffraction, scanning electron microscopy, transmission electron microscopy, energy dispersive X-ray spectroscopy, etc. These analytical characterization methods can reveal important information such as the phase composition of the composite material, the dispersion state of the filler, and the interface structure between the matrix and the filler, providing a basis for a deep understanding of the relationship between the structure and performance of the composite material. In addition, computational chemistry methods such as finite element analysis can also be used to predict the effective thermal conductivity of the composite material through numerical simulation and theoretical calculation based on the physical properties of the composite material components. By comparing the experimental results with theoretical calculations, we can deepen our understanding of the key factors affecting the thermal conductivity of composite materials.
[0005] In order to develop and prepare diamond-based graphite filler composite materials, people have adopted a variety of process methods and equipment, such as pressure infiltration, gas pressure infiltration, vacuum hot pressing sintering, spark plasma sintering (SPS), etc. These methods have examined the effects of a large number of process parameters on material properties, among which the most important performance indicators are thermal conductivity and coefficient of thermal expansion (CTE). For applications in the field of heat dissipation management, the in-plane thermal conductivity Most importantly, when the graphite filling amount exceeds 70 vol.%, it can reach more than 700 W / (m⋅K). If this type of material can be mass-produced at a relatively low cost, it is expected to gain an important position in the field of high thermal conductivity composite materials and compete with other materials currently on the market, including artificial diamond and polycrystalline diamond films. However, even under laboratory conditions, the thermal conductivity of different small-sized samples (graphite filling amount in the range of 60~80 vol.%) varies greatly, ranging from about 400 W / (m⋅K) to 735 W / (m⋅K).
[0006] The purpose of the present invention is to explore the feasibility of preparing high-quality diamond-graphite composite materials by infiltrating a diamond suspension into a porous graphite preform under high pressure. The process does not require expensive equipment, is simple, has low cost, does not require high skills for operators, and does not require complex molds. Summary of the invention
[0007] The purpose of the present invention is to provide a diamond-graphene composite material with high thermal conductivity and a preparation method thereof, so as to solve the technical problems of unstable thermal conductivity, complex preparation process and high cost of the composite material in the prior art. In the process of preparing the high thermal conductivity diamond-graphite composite material, the present invention adopts a variety of modern analytical characterization methods. The crystallinity of the graphite used is measured by X-ray diffractometer, and the diffraction spectrum is analyzed and calculated by Diffrac EVA software. The structure and components of the composite material are studied by transmission electron microscopy (TEM) and high-resolution transmission electron microscopy (HRTEM), and it is found that an amorphous transition layer is formed between the diamond matrix and the graphite sheet. The elemental composition at the interface of the composite material is analyzed by energy dispersive X-ray spectroscopy (EDX).
[0008] The technical solution of the present invention is as follows: A diamond-graphene composite material comprises a diamond matrix and graphite flakes dispersed in the diamond matrix; wherein: The volume fraction of the graphite sheet is 75%; The average orientation angle of the graphite sheet relative to the surface of the composite material is 97°, and the orientation angle distribution width is 20°; An amorphous transition layer with a thickness of 5-15 nm is formed between the diamond matrix and the graphite sheet, and the amorphous transition layer contains C, O, and Si elements; The in-plane thermal conductivity of the composite material is not less than 570 W / (m⋅K).
[0009] Furthermore, the average diameter of the graphite sheet is 300 μm and the thickness is 15 μm.
[0010] Furthermore, the carbon content of the graphite sheet is ≥99.5%, and the crystallinity is 92.8%.
[0011] Furthermore, the diamond content of the diamond matrix is ≥99.9%, and the median particle size of the diamond particles is 20 μm.
[0012] The present invention also provides a method for preparing the diamond-graphene composite material, comprising the following steps: (1) Graphite powder and silicon powder were mixed in a weight ratio of 83:17, ball-milled for 1-10 hours, and then sieved; (2) vibrating and pressing the mixed powder in a mold at a maximum pressure of 25 MPa to obtain a porous graphite preform; (3) heating the porous preform to 600° C. at a rate of 10° C. / min and keeping the temperature for 60 minutes; (4) Preparation of diamond suspension; (5) heating the diamond suspension to 900°C; (6) infiltrating the diamond suspension into the porous graphite preform under a pressure of 100 MPa; (7) Cooling and directional solidification are carried out under pressure.
[0013] In addition, the present invention quantitatively evaluates the orientation of graphite sheets in composite materials based on computational chemistry techniques. Based on the known physical properties of the composite material components (such as the in-plane / vertical thermal conductivity of graphite, the thermal conductivity of diamond, etc.), the following theoretical calculation model is used to estimate the comprehensive thermal conductivity of the composite material: ;in, is the in-plane thermal conductivity of the graphite sheet in the composite material, is the in-plane thermal conductivity of graphite, is the average deviation angle of the normal line of the graphite sheet relative to the normal line of the composite surface, is the standard deviation of the orientation angle distribution.
[0014] Considering that graphite sheets are dispersed in the diamond matrix, The influence of the thermal resistance of the diamond / graphite interface needs to be considered, and its effective value is calculated using the following formula: ;in, is the thermal conductivity of the diamond / graphite interface, is the average diameter of graphite flakes.
[0015] The calculated value of formula (4) is Substituting into formula (3), we can get the average in-plane thermal conductivity of the graphite sheets in the composite material: Combined with the volume fraction of graphite and the thermal conductivity of the diamond matrix, the comprehensive thermal conductivity of the composite material can be calculated using the mixing law. These analytical characterizations and theoretical calculation results provide important basis for revealing the microscopic mechanism of the high thermal conductivity of the composite material of the present invention.
[0016] Beneficial effects of the present invention: 1. The present invention adopts a vibration pressing process to prepare a porous graphite preform, which significantly improves the orientation of graphite sheets and increases the thermal conductivity of the composite material to 570-625W / (m⋅K), and the performance is stable, and the dispersion is controlled within ±5%.
[0017] 2. The present invention forms a nano-scale amorphous transition layer between the diamond matrix and the graphite sheet, which effectively improves the interface bonding, reduces the interface thermal resistance, and improves the comprehensive thermal conductivity of the composite material.
[0018] 3. The preparation process of the present invention is simple, does not require expensive equipment, and does not require complex molds, has low production costs and good industrial application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 is the thermal conductivity of diamond-graphite composites prepared with and without vibration pressing process; Figure 2 The Fourier transform pattern of the interface HRTEM of diamond particles and graphite substrate; Figure 3 Image processing for graphite lamella orientation: (a) optical micrograph of a composite material cross section with a 5 mm × 5 mm field of view (b) histogram of graphite lamella orientation angle distribution and Gaussian fitting curve. DETAILED DESCRIPTION
[0020] The raw materials used in the present invention include: high-quality flake graphite powder, silicon powder, diamond powder, and high-purity diamond suspension. The parameters and characteristics of the main raw materials are shown in Table 1.
[0021] Table 1 Characteristic parameters of main raw materials The crystallinity of graphite is 92.8%, which is measured by X-ray diffractometer Bruker D2Phaser, and the diffraction pattern is analyzed and calculated by Diffrac EVA software.
[0022] The process steps for preparing the porous graphite preform are as follows: 83wt.% graphite powder and 17wt.% silicon powder are mixed in a Glen Mills ball mill for 1-10 hours and then sieved (mesh size is 2mm × 2mm). The mixed powder is layered and pressed in a high-temperature resistant metal mold with a maximum pressure of 25MPa. For vibration pressing, a Cleveland Vibrator vibration table with frequency and amplitude adjustment is used.
[0023] The metal high temperature mold containing the porous graphite preform was placed in a Carbolite muffle furnace and heated to 600°C at a rate of 10°C / min and kept at this temperature for 60min. The diamond suspension was heated to 900°C in a PyroGenesis plasma melting furnace. The porous graphite preform was infiltrated using an APEX 3010 digital press with a pressure of up to 100MPa, and the infiltration was carried out according to a preset loading curve. The composite block was cooled and directionally solidified under pressure, and the cooling process was achieved using the water-cooled base of the press.
[0024] The composite blocks were cut, ground and polished using a Struers Secotom-15 cutter and a Tegramin-25 automatic grinder and polisher. The density of the composites was determined by immersion using a Mettler Toledo XPE204 analytical balance. The specific heat capacity and thermal conductivity were determined using a NETZSCH LFA 467HyperFlash instrument. The structure and composition of the composites were studied using a FEI Talos F200X transmission electron microscope (TEM) and a high-resolution transmission electron microscope (HRTEM). The elemental composition was analyzed using energy dispersive X-ray spectroscopy (EDX). A focused ion beam (FIB) was used to treat any area of the sample and a cross section was prepared, which was then further analyzed using a scanning electron microscope (SEM) and EDX.
[0025] like Figure 1 As shown, the in-plane thermal conductivity of the composite samples prepared under the same process conditions is The measurement results are quite different. We speculate that the difference in the orientation of graphite sheets may cause this phenomenon. Vibration pressing is a commonly used method to improve the order of particle arrangement. Introducing vibration pressing when preparing graphite preforms can not only reduce the discreteness of thermal conductivity, but also significantly increase the absolute value of thermal conductivity. Figure 1 The test results of thermal conductivity of composite samples prepared with and without vibration pressing process are given.
[0026] In-plane thermal conductivity of composite samples without vibration pressing The in-plane thermal conductivity of the samples after vibration pressing is within the range of 400~550W / (m⋅K), while the in-plane thermal conductivity of the samples after vibration pressing is increased to 570~625W / (m⋅K). This result shows that by optimizing the vibration pressing process, the dispersion of thermal conductivity performance indicators can be controlled within ±5%, greatly improving the stability and consistency of composite material performance.
[0027] In order to analyze the influence of process factors and microstructure (graphite sheet orientation) on the thermal conductivity of composite materials, we selected a vibrating pressed graphite sheet with an in-plane thermal conductivity of The composition and microstructure of the sample with a power of 581W / (m⋅K) were characterized in detail. The interface between the diamond matrix and the graphite layer was studied in detail. EDX analysis showed that the interface area mainly contained elements such as C, O, and Si. HRTEM photos are shown in Figure 1. Figure 2 The results show that the thickness of the interface layer is about 10nm. Fourier transform of this area obtained relatively diffuse diffraction rings, indicating that the interface layer is amorphous. The contrast of the diffraction rings is uniform and continuous, without obvious diffraction spots, indicating that there is no crystalline phase in the interface layer. The carbon-containing area is composed of a layered structure, and the calculated interlayer spacing is between 0.365 and 0.370nm, which is close to the (111) interplanar spacing of graphite (d111=0.335nm, JCPDS 41-1487) but there is a certain difference, which may be caused by the deformation of graphite during the sample preparation process.
[0028] The above results show that a very thin (5-15 nm) amorphous transition layer is formed at the interface between diamond and graphite. The mutual diffusion of C, O, and Si atoms through the interface was observed. The amorphous structure of the interface layer may be due to the thin transition layer. Under the action of high temperature for a short time, the amount of reacting substances is not enough to form a complete crystal structure. This quasi-liquid amorphous transition layer can enhance the bonding between diamond and graphite sheets and improve the thermal conductivity of the interface.
[0029] In order to quantitatively evaluate the orientation of graphite flakes, we cut a sample from the composite material block parallel to the pressing direction and polished its surface to make the orientation of the graphite flakes clearly visible. A 30mm×30mm field of view was selected in the center of the sample and divided into 6×6 small areas of 5mm×5mm. Only graphite flakes with a thickness of no more than 25μm were examined. The cross-section of graphite flakes usually appears as long and thin strips, sometimes slightly curved. In order to facilitate subsequent image processing, the outline of the graphite flakes was first identified and extracted using software, and the background was eliminated (see Figure 3 ). Then the Hough transform algorithm is used to detect straight lines in the image.
[0030] The graphite layer orientation angle data obtained by image processing is fitted with a Gaussian function: (1) In the field of view, there are 24 Gaussian fits with standard deviations , the rest of the data are discarded. For the composite material sample studied, the average deviation angle of the normal direction of the graphite sheet relative to the normal direction of the sample surface is 97 degrees, and the average width of the orientation angle distribution is 20 degrees. Using the orientation angle distribution function and the anisotropic thermal conductivity of graphite, the average thermal conductivity of the graphite sheet of the composite material in the measurement direction can be calculated: (2) (3) in, is the in-plane thermal conductivity of graphite, is the vertical thermal conductivity of graphite, , rad. The following points are considered in formula (3): For the composite material of the present invention, , and .
[0031] Since graphite sheets are dispersed in the diamond matrix, Taken as the effective value considering the thermal resistance of the diamond / graphite interface (4) Take W / (m⋅K), average diameter of graphite flakes μm, thermal conductivity of diamond / graphite interface W / (m²⋅K), substituting into formula (4) we get W / (m⋅K). Substituting it into formula (3) we can get the average thermal conductivity of the graphite sheets in the composite material: W / (m⋅K). The volume fraction of graphite is 75%, and the thermal conductivity of the matrix diamond is 2200W / (m⋅K). The mixed law is used to estimate the comprehensive thermal conductivity of the composite material. W / (m⋅K). This calculated value is slightly higher than the measured value W / (m⋅K), this deviation is acceptable.
[0032] The present invention successfully prepares a high thermal conductivity diamond-graphite composite material by infiltrating a porous graphite preform with a diamond suspension under high pressure. By optimizing the process parameters, a uniform, dense, pore-free, and third-phase-free composite material is obtained. A very thin (5-15 nm) amorphous transition layer is formed between the diamond matrix and the graphite sheet, which promotes interface bonding and reduces interface thermal resistance.
[0033] The introduction of vibration pressing process can significantly improve the orientation of graphite sheets, and obtain a highly oriented structure with an average orientation angle of 97° and an orientation angle distribution width of 20°. When the graphite volume fraction is 75%, the in-plane thermal conductivity of the composite material reaches 581W / (m⋅K), which is close to the theoretical estimated value.
[0034] In summary, by infiltrating a diamond matrix with an oriented porous graphite preform obtained by vibration pressing, a diamond-graphite composite material with excellent thermal conductivity and obvious anisotropy can be prepared. By further optimizing the composition and microstructure of the composite material, it is expected to obtain a new type of thermal conductive composite material with higher thermal conductivity and more stable performance, which has broad application prospects in the field of heat dissipation.
Claims
1. A diamond-graphene composite material, characterized in that: The composite material comprises a diamond matrix and flake graphite dispersed in the diamond matrix, wherein: The volume fraction of the flake graphite is 75%; The average orientation angle of the flake graphite relative to the surface of the composite material is 97°, and the standard deviation of the orientation angle distribution is 0.35 radians; An amorphous transition layer with a thickness of 5-15 nm is formed between the diamond matrix and the flake graphite; The in-plane thermal conductivity of the composite material is 570-625 W / (m·K).
2. The composite material according to claim 1, characterized in that: The flake graphite has a diameter of 300 μm and a thickness of 15 μm.
3. The composite material according to claim 1, characterized in that: The carbon content of the flake graphite is ≥99.5%, and the crystallinity is 92.8%.
4. The composite material according to claim 1, characterized in that: The diamond matrix is composed of diamond micropowder with a particle size of 20 μm, and the diamond content of the diamond micropowder is ≥99.9%.
5. The composite material according to claim 1, characterized in that: The in-plane thermal conductivity of the composite material is 581 W / (m·K).
6. The method for preparing the composite material according to any one of claims 1 to 5, characterized in that: The method comprises the following steps: (1) Mix flake graphite powder and silicon powder in a mass ratio of 83:17, ball mill for 1-10 hours and pass through a 200 mesh sieve; (2) vibrating and pressing the mixture at a pressure of 25 MPa to obtain a porous preform; (3) heating the porous preform to 600° C. at a rate of 10° C. / min and keeping the temperature for 60 minutes; (4) Preparation of diamond suspension; (5) heating the diamond suspension to 900° C. (6) infiltrating the diamond suspension into the porous preform under a pressure of 100 MPa; (7) Cooling and directional solidification are carried out under pressure.